Noise Removal and Contrast Enhancement for X-Ray Images - Huang, Ren-You; Dung, Lan-Rong; Chu, Cheng-Fa; Wu, Yin-Yi (British Journal of Healthcare and Medical Research, 2016)
<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: SimSun; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">X-ray image play<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: 新細明體; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: ZH-TW; mso-bidi-language: AR-SA; mso-fareast-theme-font: minor-fareast;" lang="EN-US">s a<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: SimSun; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> very important role in the medical diagnosis. To help the doctors for diagnosis of the disease, some algorithms for enhancing X-ray images were proposed in the past decades. However, the enhancement of images will also amplify the noise or produce distortion of image, which are unfavorable to the diagnosis. Therefore, appropriate techniques <span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: 新細明體; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: ZH-TW; mso-bidi-language: AR-SA; mso-fareast-theme-font: minor-fareast;" lang="EN-US">for<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: SimSun; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> noise suppression and contrast enhancement are necessary. This paper proposed an algorithm <span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: 新細明體; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: ZH-TW; mso-bidi-language: AR-SA; mso-fareast-theme-font: minor-fareast;" lang="EN-US">including t<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: SimSun; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">wo-stage filtering <span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: 新細明體; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: ZH-TW; mso-bidi-language: AR-SA; mso-fareast-theme-font: minor-fareast;" lang="EN-US">and contrast enhancement <span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: SimSun; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">for X-ray images. By using adaptive median filter and bilateral filter, our method is able to suppress the mixed noise which contains Gaussian noise and impulsive noise, while preserving the important structures (e.g., edges) in the images. Afterwards, the contrast of image is enhanced by using gray-level morphology and contrast limited histogram equalization (CLAHE). In<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: 新細明體; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: ZH-TW; mso-bidi-language: AR-SA; mso-fareast-theme-font: minor-fareast;" lang="EN-US"> the<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: SimSun; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> experiments, we evaluate the performance of noise removal and contrast enhancement separately with quantitative indexes and visual results. For the mixed noise case, our method <span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: 新細明體; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: ZH-TW; mso-bidi-language: AR-SA; mso-fareast-theme-font: minor-fareast;" lang="EN-US">is able to<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: SimSun; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> achieve averaged PSNR 39.89 dB and averaged SSIM 0.9449<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: 新細明體; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: ZH-TW; mso-bidi-language: AR-SA; mso-fareast-theme-font: minor-fareast;" lang="EN-US">; for the contrast enhancement, our method is able to enhance more detail structures (e.g., edges, textures) than CLAHE.